Isolation, characterization and antibiogram studies of bacteria isolated from ready-to-eat foods sold at different places of Dinajpur district, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2023)
Ready-to-eat (RTE) foods are widely used at home, restaurants, and during festivals in Bangladesh. Foodborne illness is very common and mainly caused by the consumption of contaminated street foods. It is very important to investigate possible microbial contamination in RTE foods. The present study was conducted to isolate and characterize bacterial pathogens from RTE foods and to know the antimicrobial susceptibility patterns of the isolated bacteria. A total of 60 RTE food samples for instance, burger, fuchka, fried rice, and chicken grill (fifteen samples each) were collected aseptically from street food vendors of different locations at Dinajpur. Bacteria were isolated and identified based on cultural, staining, and biochemical properties following standard microbiological methods. Among four types of tested RTE foods, 100% comprised of bacterial contamination. The total viable count (TVC) in burger ranged from 4.2×103 to 1.6×104; in fuchka ranged from 4.5×103 to 2.5×104; in fried rice ranged from 4.7×103 to 1.5×104; and in chicken grill ranged from 4.9×103 to 1.6×104. Among the tested RTE food samples, Escherichia coli 6 (10%), Salmonella spp. 7 (11.66%), and Klebsiella spp. 2 (3.33%) were isolated. Antibiogram studies revealed that Streptomycin, Gentamicin, Tetracycline, and Neomycin were found sensitive for both of the isolated E. coli and Klebsiella spp. On the other hand, Streptomycin, Azithromycin, Gentamicin, Tetracycline, and Neomycin were found sensitive for Salmonella spp. Vancomycin, Penicillin, Erythromycin, Amoxicillin, and Ampicillin were found resistant for E. coli and Salmonella spp. isolates, whereas Vancomycin, Azithromycin, Penicillin, Erythromycin, Amoxicillin, and Ampicillin were found resistant for Klebsiella spp. The results of this study suggested that RTE foods should be manufactured under good hygienic practices.Asian Australas. J. Food Saf. Secur. 2023, 7 (1), 1-9